Eficácia de serviços em saúde mental com o uso de m-Health na COVID-19 - Secchi, Álisson (2022)
The Covid-19 has focused on mental health problems and as general conditions of mental health and as general conditions of an emergency of stress levels, symptoms of anxiety, depression, especially in more care services of special attention the need to offer online services. The present dissertation had as general objective the company mental health services with the use of mental health services in Covid-19 triggered by professionals. As general health assessment subjects, the use of general health indicators and assessment of relevant mental health aspects before and relevant online mental health assessment tools; b) to verify the effects of remote interventions, with the Balint group, as emotional support to health professionals. “Balint groups with the use of m-Health in Covid-19” sought to evaluate the contributions of Balint groups with health professionals with an m-Health-19 device. It is a developed study, carried out in three phases: initial assessment, online intervention, reassessment. Eight health professionals participated in the study, aged between 20 and 59 years, of different genders and levels of education, coming from public and/or private institutions, from the three levels of health care in Rio Grande do Sul. 1. The following instruments were used: a) Demographic questionnaire to characterize the sample; b) Questionnaire for mental health assessment (SRQ- 20); c) Depression, Anxiety and Stress Scale (DASS-21); d) Covid-19 Fear Scale (FCV-19S); e) Post Traumatic Stress Disorder Checklist (PCL-C). The results responded to the proposed objective and referred to contributions from mental health services aimed at health professionals. Balint groups concerned and concerned about the troubling symptoms presented, especially in the easing of the Covid19 pandemic. The results of this offer of practices in remote mental health and incentive to study research with expanded extensions so that they can contribute to public policies proposed for the promotion of mental health professional in health.